Peran Guru dalam Menanamkan Jiwa Kreatif dan Inovatif Berwirausaha Peserta Didik melalui Pembelajaran Prakarya di Sekolah Dasar - Vina Nurul Ramadanti; Mayang Sari; Lala Khadijah; Dadan Nugraha (Universitas Negeri Padang, 2022)
This research determined the teacher's role in instilling the creative and innovative spirit of entrepreneurship in students through craft learning. This research uses descriptive research with a qualitative approach. The data is used in the form of qualitative data. The subject of this study was the fifth-grade teacher at SDN Malingping, Sumedang. The procedure carried out in this study starts from the description, reduction, and selection stages. Data collection techniques and instruments are interviews, observation, and documentation. The data analysis used is reduction, data display, conclusion, and drawing/verification Based on the results of the study, it was found that the teacher's role in cultivating a creative and innovative spirit of entrepreneurship is reflected in learning crafts. Craft learning is carried out in line with the applicable curriculum. In craft learning, the attitudes that are developed are skilled, creative, and innovative attitudes that can continuously foster the entrepreneurial spirit of students.